Modeling of variability of hydrological characteristics of the Tuzla group of lagoons under various variants of their water exchange with the sea - Yu. S. Tuchkovenko; D. V. Kushnir (Український гідрометеорологічний журнал, 2022)
The article is devoted to solving the problem of stabilization of hydrological regime and hydro-ecological conditions of the Tuzla group of lagoons located in the central part of the Danube-Dniester interfluve by ensuring and regulating their water exchange with the open sea through artificially created channels in the barrier beach that separates the water body from the sea.